HIASAN DINDING ESTETIKA DARI LIMBAH SEKAM PADI - Andi Muhamad Iqbal Akbar Asfar; Andi Muhammad Irfan Taufan Asfar; Sharma Thaha; Ady Kurnia; Andi Nurannisa; Vivi Elvira Ekawati; Sartika Sari Dewi (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The problem of rice husk waste becomes crucial in Sanrego Village, especially in the Farmers Group in Elo' (partner). Community Partnership Program (PKM) activities focus on processing rice husk waste into aesthetic wall hangings. The method of implementation in the activity of PKM begins with counseling, and then training and mentoring are carried out. The results of the implementation of PKM activities to partners showed a significant increase in knowledge and information about the benefits of rice husk waste, and there was also an improvement in the skills of partners in processing rice husk waste into aesthetic wall hangings using natural dyes obtained from herbal ingredients such as turmeric, pandan leaves, dragon fruit skin, and coffee. Increased knowledge and skills in making aesthetic wall hangings reached 100%.